Improving the Stability and Catalyst Lifetime of the Halogenase RebH Using Directed Evolution - Poor, Catherine B. (2014)
We previously reported that the halogenase RebH catalyzes selective halogenation of several heterocycles and carbocycles, but product yields were limited by enzyme instability. Here, we use directed evolution to engineer a RebH variant, 3-LR, with a T(opt) over 5 °C higher than that of wild type, and 3-LSR, with a T(m) 18 °C higher than that of wild type. These enzymes provided significantly (up to 4-fold) improved conversions for halogenation of tryptophan and several non-natural substrates. This initial demonstration of RebH evolution not only provides improved enzymes for immediate synthetic applications, but also establishes a robust protocol for further halogenase evolution.